A novel Pyroptosis‐related long non‐coding RNA signature for predicting the prognosis and immune landscape of head and neck squamous cell carcinoma. (14th May 2022) - Zhou, Chongchang; Shen, Yiming; Jin, Yangli; Shen, Zhisen; Ye, Dong; Shen, Yi; Deng, Hongxia
Abstract: Background: Pyroptosis plays an essential function in carcinogenesis and the antitumor immune response. Herein, we constructed a pyroptosis‐related long noncoding RNA (prLncRNA) signature to predict therapeutic effects and outcomes for head and neck squamous cell carcinoma (HNSCC) patients. Methods: Patients obtained from the TCGA‐HNSC project were divided randomly into the training as well as the validation sets at a ratio of 7:3. A novel prognostic prLncRNA signature was constructed from the results of the training set using the least absolute shrinkage and selection operation. The medium value was used as the basis for categorizing all HNSCC patients into a low‐ or high‐risk cohort. Cox regression and Kaplan–Meier (KM) survival analyses were executed to estimate the prognostic value. We also evaluated the functional enrichment, tumor microenvironment, immune cell infiltration, and the sensitivity to chemotherapy and immunotherapy between the high‐ and low‐risk cohorts. Results: Nineteen prognostic prlncRNAs were identified to establish the prognostic signature. Multivariate Cox regression and KM survival analyses confirmed that this prlncRNA signature might serve as an independent prognostic indicator of patient survival, which was subsequently confirmed using a validating dataset. Multiple ROC curves indicated the prlncRNA signature presented a more predictive power than clinicopathological factors (age, sex, tumor grade, and tumor stage). GO, KEGG, and GSEA enrichment analysis disclosed several immune‐related pathways which appeared to be enhanced in the low‐risk cohort. ESTIMATE, CIBERSORT, and ssGSEA algorithms indicated considerable differences in the tumor microenvironment and immune cell infiltration in the low‐ and high‐risk cohorts. Furthermore, the low‐risk cohort was predicted to achieve a better response to immunotherapeutic drugs, while in contrast, the high‐risk cohort would be more sensitive to chemotherapy drugs. Conclusions: Our findings robustly demonstrate that our constructed prlncRNA signature could serve as an efficient indicator of prognosis, immunotherapy response, and chemosensitivity for HNSCC patients. Abstract : our findings robustly demonstrate that our constructed prlncRNA signature could serve as an efficient indicator of prognosis, immunotherapy response, and chemosensitivity for HNSCC patients.